Perbedaan Tingkat Kesegaran Jasmani Siswa SD Negeri 13 Muara Siberut Dengan Siswa SD Negeri 06 Rogdog Kecamatan Siberut Selatan - Meiriani Armen (Universitas Negeri Medan, 2017)
The research aims to explain differences in physical fitness level of student SD Negeri 13 Muara Siberut with siswa SD Negeri 06 Rogdog subdistrict South Siberut. This type of research is computational. The population in this study is a classroom V SD Negeri 13 Muara Siberut dengan SD Negeri 06 Rogdog subdistrict South Siberut. Techniques used in the sampling is random sampling technique, which is sampling conditional. Thus the number of samples in this study is much 25 people female student. Techniques of data retrieval is done by testing TKJI (Tingkat Kesegaran Jasmani Indonesia) or the level of physical fitness Indonesia. Data were analyzed using mean difference test or t-test. The data analysis technique used is the difference (t-test). By using t-test, apparently there are thitung (2,26) while talpha (1,88) with level 0,05 mean thitung (2,66) > talpha (1,88) so that Ho rejected dan Ha be accepted, so in conclusion there are different level of physical fitness of student SD Negeri 13 Muara Siberut dengan SD Negeri 06 Rogdog subdistrict South Siberut.